A Dehydrogenase Dual Hydrogen Abstraction Mechanism Promotes Estrogen Biosynthesis: Can We Expand the Functional Annotation of the Aromatase Enzyme?. Issue 42 (25th June 2018) - Spinello, Angelo; Pavlin, Matic; Casalino, Lorenzo; Magistrato, Alessandra
Abstract: Cytochrome P450 (CYP450) enzymes are involved in the metabolism of exogenous compounds and in the synthesis of signaling molecules. Among the latter, human aromatase (HA) promotes estrogen biosynthesis, which is a key pharmacological target against breast cancers. After decades of debate, interest in gaining a comprehensive picture of HA catalysis has been renewed by the recent discovery that compound I (Cpd I) is the reactive species of the peculiar aromatization step. Herein, for the first time, a complete atomic‐level picture of all controversial steps of estrogen biosynthesis is presented. By performing cumulative quantum‐classical molecular dynamics and metadynamics simulations of about 180 ps, it is revealed that the most likely enzymatic path relies on three factors: 1) androstenedione enolization and compound 0 (Cpd 0) formation through a proton network mediated by Asp309; 2) subsequent formation of Cpd I, upon rearrangement of the Asp309 side chain and the establishment of a proton network involving Asp309 and Thr310; and 3) after two hydroxylation reactions, 19, 19‐ gem ‐diol is converted into estrone by Cpd I, through an uncommon dehydrogenase‐like dual hydrogen abstraction mechanism. As a result, HA performs estrogen biosynthesis by merging hydroxylase with dehydrogenase activity, which suggests that the need to perform complex chemical transformations led nature to engineer HA, and possibly other steroidogenic CYP450s, by expanding its range of functions to achieve an optimal catalytic efficiency. Abstract : Defining reaction steps : Human aromatase (HA) promotes the conversion of androgens into estrogens through a three‐step catalysis process (see figure). The molecular mechanism of estrogen biosynthesis was unveiled by performing classical and mixed quantum‐classical metadynamics simulations to elucidate that, similarly to other CYP450, the substrate is converted into estrone through an uncommon dehydrogenase‐like dual hydrogen abstraction mechanism.